PENDEKATAN REALISTIK MATEMATIKA EDUCATION DALAM MENINGKATKAN KEMAMPUAN KONEKSI MATEMATIKA - Patrisia Trilasmini; Prayuniningtyas A.W (Jurnal Pendidikan Dasar, 2018)
ction research aims to improve mathematical connection skills in Air Periukan sub-district, Seluma Bengkulu. This research method uses the Action Research Method. The subjects in this study were class VI elementary school students, amounting to 25 students. This research was conducted for one month, this study consisted of two cycles and each cycle consisted of four meetings. In the first cycle there was an increase in good movement in children, but there were still children who had not yet completed the increase in mathematical connection skills with 15 in criteria are less, 10 children are included in the criteria of good. .In the second cycle based on the results of teacher assessment and an increase in cyclical 2 with a number of 16 good students and 9 students who are lacking. In the third cycle declared complete. From this study it can be concluded that through the RME approach can improve mathematical connection skills in class VI students of SD 83 Seluma elementary school